Generate Financial Reports for Micro, Small and Medium Enterprises (MSMEs) Using Microsoft Excel - Nindy Irzavika; Kharisma Wiati Gusti; Novi Trisman Hadi; Fadhli Suko Wiryanto; Muhammad Panji Muslim (Universitas Pendidikan Ganesha, 2025)
MSMEs struggle with basic financial practices such as recording transactions and preparing financial reports, leading to inaccurate data and poor decision-making. This research uses Microsoft Excel as the main tool to produce a practical and efficient method for preparing financial reports for Micro, Small, and Medium Enterprises (MSMEs). The method used in this research is participatory, qualitative descriptive, which seeks to actively involve MSME actors in the Haur Pancuh II Culinary Tourism Village. The method used in this research is a case study. The data obtained was analyzed using qualitative descriptive analysis, namely by systematically describing the results of observations and interviews. The analysis process includes data reduction, data presentation, and concluding. Results showed significant improvements in participants' financial literacy, increased understanding of financial reporting, and confidence in applying their knowledge. This research underscores the importance of tailored financial literacy programs in empowering MSMEs to improve their financial management practices. These findings have practical implications for policymakers, educators, and community leaders aiming to increase the resilience and competitiveness of MSMEs through targeted capacity development initiatives, paving the way for more sustainable economic development in similar contexts.